Prevalence of ecosapentaenoic acid and docosahexaenoic acid deficiency in pregnant women: a prospective observational study - Mishra, Vishwa J.; Nayar, Sakshi; Mansukhani, Chandra; Kumar, Sunita; Gujral, Kanwal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Docosahexaenoic acid (DHA), ecosapentaenoic acid (EPA) and alpha lineoloic acid (α-LA) are essential fatty acids of the long chain polyunsaturated fatty acid (LC-PUFA) or omega-3 fatty acid. These fatty acids are not synthesized by our body. Diets rich in LC-PUFA reduces the incidence of - preeclampsia, intrauterine growth restriction, preterm delivery, in utero fetal death and placental abruption. Objectives of the study were: to estimate the prevalence of EPA and DHA deficiency in pregnant women by omega-3 index test (O3I), and also to correlate blood levels of EPA and DHA with various socio demographic parameters. Methods: All enrolled subjects were assessed with a pre-defined performa for their demographic and socio-economic characteristics, personal history, obstetric history, body mass index (BMI), education, diet and blood samples were tested for O3I. Results: Result of the study indicated that 98% of pregnant women had EPA and DHA deficiency as indicated by O3I levels. This was regardless of age, parity, BMI, and socio economic status. Women consuming vegetarian diet had statistically significant lower mean and median levels of O3I as compared to the women having a non-vegetarian diet, p value <0.001, 0.004 respectively. In our entire cohort of 150 women, only 2 non-vegetarian women had sufficient O3I. Conclusions: 98% of pregnant women across various socio economic classes had EPA and DHA deficiency as measured by O3I levels. Vegetarians had statistically significant lower levels of O3I as compared to the non-vegetarians.